Peran Keluarga dan Sekolah dalam Deteksi Dini Perilaku Bermasalah pada Remaja: Sebuah Tinjauan Literatur - Galuh Nabila Audry Rahmania; Rafeylah Areefa Elya; Anasari Anasari; Afiyah Nasywa Apezahli; Lidiana Rahayu Ningsih; Muhammad Roihan; Rizki Novirson (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Adolescence is a transitional stage of development characterised by rapid biological, psychological, and social changes that increase vulnerability to the emergence of problematic behaviour. The increase in cases of juvenile delinquency highlights the importance of early detection as a prevention strategy. This study aims to examine the role of families and schools in the early detection of problematic behaviour in adolescents through a systematic literature review. The study used a systematic literature review method by analysing scientific articles published between 2021 and 2026 that discussed family involvement, the role of schools, and early detection of adolescent behaviour. Data were collected through a structured process of searching, selecting, critically evaluating, and synthesising the literature. The results showed that family factors such as parenting styles, emotional support, communication quality, and supervision have a significant influence on adolescent behavioural development. Schools also play a strategic role through counselling services, behavioural screening, mental health education, and collaborative interventions. Effective early detection occurs when families and schools work together through continuous communication and coordinated monitoring. Therefore, the role of families and schools is to strengthen efforts to identify and prevent behavioral problems so that interventions can be carried out more quickly to support the social and emotional well-being of adolescents. Strengthening collaboration and structured detection systems are important steps in reducing the risk of problematic behaviour in adolescents.